Rethinking Hanslick music, formalism, and expression - Grimes, Nicole; Donovan, Siobhán 1966-; Marx, Wolfgang 1967- (Boydell & Brewer, 2013)
Rethinking Hanslick: Music, Formalism, and Expression' is the first extensive English-language study devoted to Eduard Hanslick--a seminal figure in nineteenth-century musical life. Bringing together eminent scholars from several disciplines, this volume examines Hanslick's contribution to the aesthetics and philosophy of music and looks anew at his literary interests. The essays embrace ways of thinking about Hanslick's writings that go beyond the polarities that have long marked discussion of his work such as form/expression, absolute/program music, objectivity/subjectivity, and formalist/hermeneutic criticism. This approach takes into consideration both Hanslick's important 'On the Musically Beautiful' and his critical and autobiographical writings, demonstrating Hanslick's rich insights into the context in which a musical work is composed, performed, and received. 'Rethinking Hanslick' serves as an invaluable companion to Hanslick's prodigious scholarship and criticism, deepening our understanding of the major themes and ideas of one of the most influential music critics of the nineteenth century. Dr Nicole Grimes is a Marie Curie Fellow at University College Dublin (UCD), and the University of California, Irvine. Dr Siobhán Donovan is a College Lecturer at the School of Languages and Literatures, UCD. Dr Wolfgang Marx is a Senior Lecturer at the School of Music, UCD.
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Hanslick, Eduard / 1825-1904; Hanslick, Eduard -- 1825-1904; Geschichte 1800-1900; Geschichte 1800-1904; Geschichte; Musik; Music / 19th century / Philosophy and aesthetics; Musical criticism / History / 19th century; Musikkritik; Wien; Aufsatzsammlung